The Maternal Body Fluids and Amniotic Fluid in Near Term Pregnancies - Sümeyra Nergiz Avcıoğlu; Sündüz Özlem Altınkaya; Mert Küçük; Selda Demircan Sezer; Emre Zafer; Hasan Yüksel (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to investigate the relationship between amniotic fluid volume and mainly volume of maternal body fluid compartments and secondly maternal obesity in near term pregnancies.